3D Printed Biocatalytic Living Materials with Dual‐Network Reinforced Bioinks. Issue 6 (2nd December 2021) - He, Fukun; Ou, Yangteng; Liu, Ji; Huang, Qiu; Tang, Bao; Xin, Fengxue; Zhang, Jing; Jiang, Min; Chen, Su; Yu, Ziyi
Abstract: The field of living materials seeks to harness living cells as microfactories that can construct a material itself or enhance the performance of material in some manner. While recent advances in 3D printing allow microbe manipulation to create bespoke living materials, the effective coupling of these living components in reinforced bioink designs remains a major challenge due to the difficulty in building a robust and cell‐friendly microenvironment. Here, a type of dual‐network bioink is reported for the 3D printing of living materials with enhanced biocatalysis capabilities, where bioinks are readily printable and provide a biocompatible environment along with desirable mechanical performance. It is demonstrated that integrating microbes into these bioinks enables the direct printing of catalytically living materials with high cell viability and maintains metabolic activity, which those living materials can be preserved and reused. Further, a bacteria‐algae coculture system is fabricated for the bioremediation of chemicals, giving rise to its potential field applications. Abstract : A class of dual‐network reinforced bioink is developed for 3D printing of a bespoke living material with enhanced biocatalysis capabilities. The microbes in the 3D lattices can maintain high cell viability and metabolic activities in fermentation and bioremediation processes.